Analysis of Bilingual Learning Media in Mathematics Subjects for Elementary School Students - Lathifah, Laily Ainun; Rahayu, Erviana Tri; Putri, Najwa Rheina; Kediri, Shafira Ratu Sekartaji Putri; Fauzika, Sherly Putri; Pradana, Feranika Putri; Widagdo, Arif (Lembaga Riset Mutiara Akbar, 2025)
This research aims to analyze bilingual learning media in mathematics subjects for elementary school students. This type of research is qualitative research with a literature study method from various scientific journals that discuss bilingual learning media, especially in mathematics subjects at the elementary school level. Bilingual learning media is learning media that presents material in two languages such as native language and foreign language. The purpose of bilingual learning media is to facilitate students in understanding the material and improving foreign language skills. There are 3 types of bilingual learning media that can be applied to learning mathematics in elementary schools, namely concrete, visual, and audio-visual media. Using bilingual learning media in mathematics learning at the elementary school level can improve foreign language skills and the problem-solving process in the learning process so that it can improve cognitive abilities.